Physiotherapeutic Performance in the rehabilitation of elderly health (Research, Society and Development, 2022)
The aging of society is a world event, starting in developed nations, and has taken on great proportions in moderate and low income territories, especially Brazil. A representation of the growing group of elderly people, compared to the youth population in Brazil, is the “ageing index”, which will grow from 43.19% in 2018 to 173.47% in 2060. : To analyze the physiotherapeutic care in the rehabilitation of the health of the elderly. This study was a narrative literature review using selected articles dated from the last 10 years (January 2011 to June 2021), found in the Google Academic, Latin American and Caribbean Literature - LILACS and Cochrane Library databases on the website of Virtual Health Library - BIREME, Scientifc Electronic Library Online - SCIELO, dissertations and theses were also consulted. Thus, the various psychological, social, and bodily changes suffered by the elderly person must be assisted in the best possible way both within the government, with the increase and progress of public policies, as well as the training of health professionals.